Service Delivery and Patient Outcomes in Ryan White HIV/AIDS Program-Funded and -Nonfunded Health Care Facilities in the United States - Weiser, John; Beer, Linda; Frazier, Emma L; Patel, Roshni; Dempsey, Antigone; Hauck, Heather; Skarbinski, Jacek (JAMA internal medicine, 2015)
Outpatient human immunodeficiency virus (HIV) health care facilities receive funding from the Ryan White HIV/AIDS Program (RWHAP) to provide medical care and essential support services that help patients remain in care and adhere to treatment. Increased access to Medicaid and private insurance for HIV-infected persons may provide coverage for medical care but not all needed support services and may not supplant the need for RWHAP funding. To examine differences between RWHAP-funded and non-RWHAP-funded facilities and in patient outcomes between the 2 systems. The study was conducted from June 1, 2009, to May 31, 2012, using data from the 2009 and 2011 cycles of the Medical Monitoring Project, a national probability sample of 8038 HIV-infected adults receiving medical care at 989 outpatient health care facilities providing HIV medical care. Data were used to compare patient characteristics, service needs, and access to services at RWHAP-funded vs non-RWHAP-funded facilities. Differences in prescribed antiretroviral treatment and viral suppression were assessed. Data analysis was performed between February 2012 and June 2015. Overall, 34.4% of facilities received RWHAP funding and 72.8% of patients received care at RWHAP-funded facilities. With results reported as percentage (95% CI), patients attending RWHAP-funded facilities were more likely to be aged 18 to 29 years (8.5% [7.4%-9.5%] vs 5.0% [3.9%-6.2%]), female (29.2% [27.2%-31.2%] vs 20.1% [17.0%-23.1%]), black (47.5% [41.5%-53.5%] vs 25.8% [20.6%-31.0%]) or Hispanic (22.5% [16.4%-28.6%] vs 12.9% [10.6%-15.2%]), have less than a high school education (26.1% [24.0%-28.3%] vs 10.9% [8.7%-13.1%]), income at or below the poverty level (53.6% [50.3%-56.9%] vs 23.9% [19.7%-28.0%]), and lack health care coverage (25.0% [21.9%-28.1%] vs 6.1% [4.1%-8.0%]). The RWHAP-funded facilities were more likely to provide case management (76.1% [69.9%-82.2%] vs 15.4% [10.4%-20.4%]) as well as mental health (64.0% [57.0%-71.0%] vs 18.0% [14.0%-21.9%]), substance abuse (33.6% [27.0%-40.2%] vs 12.0% [8.0%-16.0%]), and other support services; patients attending RWHAP-funded facilities were more likely to receive these services. After adjusting for patient characteristics, the percentage prescribed ART antiretroviral therapy, reported as adjusted prevalence ratio (95% CI), was similar between RWHAP-funded and non-RWHAP-funded facilities (1.01 [0.99-1.03]), but among poor patients, those attending RWHAP-funded facilities were more likely to be virally suppressed (1.09 [1.02-1.16]). A total of 72.8% of HIV-positive patients received care at RWHAP-funded facilities. Many had multiple social determinants of poor health and used services at RWHAP-funded facilities associated with improved outcomes. Without facilities supported by the RWHAP, these patients may have had reduced access to services elsewhere. Poor patients were more likely to achieve viral suppression if they received care at a RWHAP-funded facility.